A review of methodological choice: Research paradigm underpins - Tharsika, K.; Pratheepkanth, P. (University of Jaffna, 2020)
This paper focuses on removing the ambiguity regarding selecting the research methodology when embarking on a research project by the researcher in the social science phenomenon. Quantitative, qualitative, and mixed methods are the dominant methodologies in the social research milieu. Choosing an appropriate methodology is determined by the research paradigms (positivism, interpretive, transformative, and pragmatism). These paradigms are differentiated by the philosophical assumptions (ontology, epistemology, and research method). Therefore, the researcher should be aware of their philosophical assumptions because they inevitably shape the whole research project.
Keywords: Positivism; Interpretive; Transformative and pragmatism